Nutritional status and foliar fractions of P in coffee plants according to phosphate fertilization - Pereira Reis, Thiago Henrique; Furtini Neto, Antônio Eduardo; Guimarães, Paulo Tácito Gontijo; Guerra, Antônio Fernando; Oliveira, Cesar Henrique Caputo de (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate, in the rainy and dry seasons, the nutritional status and foliar fractions of P in coffee plants, according to phosphate fertilization, and to determine their relation with coffee yield. The cultivar Rubi MG‑1192 of Arabic coffee was used under central‑pivot, with high density (7,143 plants per ha) on Rhodic Hapludox, in the Cerrados’ region. From 2002 to 2010, the following annual doses of P were used: 0, 50, 100, 200, and 400 kg ha-1 P2O5. Foliar samples were taken after harvest, in July (dry season), and before grain filling stage, in December (rainy season). Foliar P contents were evaluated in 2009 and 2010, and the coffee yield, from 2008 to 2011. Coffee yield responded linearly to doses up to 400 kg ha-1 of P2O5. In high yielding conditions, with high P supply, foliar ranges of P are probably different from the ones reported in literature. The reserve of inorganic phosphorus in coffee leaves increases in plants with improved P supply, which ensures greater metabolic activity of plants during periods of drought stress and enables higher productivity.